Intelligence and academic achievement: an investigation of gender differences - Naderi, Habibollah; Abdullah, Rohani; Tengku Abdul Hamid, Tengku Aizan; Sharir, Jamaluddin (Marsland Press, 2010)
The objective of this research is to examine if a relationship exists between intelligence and academic achievement and if the relationship differs between males and females. Two research questions are examined in this paper: (1) what is the relationship between different aspects of intelligence and academic achievement? (2) Is there any significant gender differences regarding the relationship between different aspects of creativity and academic achievement? Participants (N=153; male=105 and female=48) completed creativity test. Cumulative grade point average (CGPA) was used to select the participants. Intelligence was measured using the Catell Culture fair Intelligence Test (CFIT-3a & b). Pearson Correlation analysis indicated that aspects of intelligence were not related to academic achievement for both males and females. However, implications of the findings for this study in intelligence and academic achievement are discussed.